The Menace of Black Money in India - Das, Dr Pradip Kumar (Archives of Business Research, 2019)
ABSTRACT Of late, the issue of black money and its consequent corruption has come into the forefront following a series of financial scandals. Black money draws conspicuous and wasteful consumption, reduces savings and grows gap between the rich and the poor. In every sphere of social, political and economic space of the country, it has a debilitating effect on the institutions of governance and conduct of public policy in India. Governance failure adversely affects the interests of vulnerable and disadvantageous sections of the society. Everybody has expressed concern on the issue especially with the publication of few reports relating to unaccounted wealth abroad. The Government of India has been pursuing to address the issue of black money in public life after noisy turmoil in Parliament. This paper is an attempt to explain the menace of black money and its aftermath consequences in India. Keywords: - Black money, Tax evasion, The Government, Unaccounted wealth, Corruption, Financial scandals.